Modifikasi Konseling Kelompok Untuk Siswa Dengan Pendekatan Rational Emotive Behavior Therapy (REBT) di Tengah Pandemi Covid-19 - Fauziah Fauziah; Neviyarni Neviyarni; Yeni Karneli; Netrawati Netrawati (Program Studi Bimbingan Penyuluhan Islam Fakultas Dakwah dan Komunikasi, 2020)
Guidance and Counseling Services is one of the services that can play an active role in the midst of this co-19 pandemic so students can adjust to conditions, in accordance with the rules set by the government, keep the spirit of learning and can control their stress and anxiety in a healthy manner. In this case the role of the BK teacher / school counselor is very important. However, various obstacles may arise in the learning process due to pandemic conditions that cannot be ascertained when it will end. This is a formidable challenge for school counselors / school counselors. One solution that can be done is to modify group counseling services using the Rational Emotive Behavioral Therapy (REBT) approach. In this article, we will discuss the modification of group counseling services for students with the Rational Emotive Behavioral Therapy (REBT) approach in the midst of the covid pandemic 19